Analysis of Redundant Building Construction Material: A Case Study for A Hospital Building Project in Bogor - Aditya Gilang Rakasiwi; Trijeti Trijeti; Rachmad Irwanto (University Of Muhammadiyah Jakarta, 2021)
Construction materials are very significant spending in a construction project. They may create losses to Implementation Budget Plan (IBP) whenever the number is excessive. This paper is intended to find causes of redundant materials for guidelines to next projects to avoid excessive number of redundant materials. This paper details driving factors to material redundancy, total value of redundant materials and percentage ratio of redundant materials total value over IBP value. To obtain those factors causing redundant materials, this research run a set of questionnaires referenced from journals and refined by expert professionals. The questionnaires set was then handed to managerial peers and other non-managerial respondents to acquire their responses. The questionnaire outcome provides clues on major driving factors. They are lack of control at site, lack of supervision and lack of allocated facility for redundant materials. Further studies in this paper using price details in IBP and unit conversion on redundant materials have come to a material redundant value of Rp. 383.940.000 from an IBP value of Rp. 31.125.169.000. The highest percentage ratio of redundant materials is from ceramics fitting works at 34.18% while total value percentage ratio of redundant materials over IBP is 1.23%.